Exploring CYGNSS mission for surface heat flux estimates and analysis over tropical oceans - Li, Xiaohui; Yang, Jingsong; Yan, Yunwei; Li, Weiqiang (Frontiers in Marine Science, 2022)
The Cyclone Global Navigation Satellite System (CYGNSS) mission can measure sea surface wind over tropical oceans with unprecedented temporal resolution and spatial coverage, so as to estimate surface latent and sensible heat fluxes (LHF and SHF). In this paper, the satellite-derived LHF/SHF estimates from CYGNSS are quantitatively evaluated and analyzed by those from the Global Tropical Moored Buoy. Comparisons of the LHF and SHF estimates demonstrate the good performance and reliability of CYGNSS heat flux products during the period of 2017–2022, including CYGNSS Level 2 Ocean Surface Heat Flux Climate Data Record (CDR) Version 1.0 and Version 1.1. Different latent heat characteristics in the tropical oceans are evaluated separately based on each buoy array, suggesting better agreement in the Atlantic for LHF/SHF products. Based on the Coupled Ocean-Atmosphere Response Experiment 3.5 algorithm, the impact of wind speed on the LHF/SHF estimates is analyzed by using the the Science Data Record V3.1 and NOAA V1.2 science wind products. The results show that the performance of satellite-derived wind speed directly affects the accuracy of LHF products, with an improvement of 17% in root-mean-square error over that of LHF CDR V1.0. Especially, in the Indian Ocean, accuracy can be improved by 26.8%. This paper demonstrates that the heat flux estimates along the orbit of the CYGNSS are an important supplement to in situ observational data and will benefit the study of global climate change.